Evaluation of retinal toxicity and efficacy of the anticytomegalovirus compound 2-amino-7-[(1,3-dihydroxy-2-propoxy)methyl]purine. - Besen, G (1995)
Compound 2242, also known as 2-amino-7-[(1,3-dihydroxy-2-propoxy)methyl]purine, is the first known antivirally active nucleoside analog with the side chain substituted at the N-7 position of the purine ring system. Our purpose was to evaluate its retinal toxicity and assess the efficacy of its highest nontoxic concentration in a rabbit model of herpes simplex retinitis. Concentrations of the drug from 0.5 to 2,000 microM were injected intravitreally in twelve New Zealand White rabbits. Fundoscopic, histologic, and electrophysiologic data revealed no evidence of toxicity even at the highest dose of the compound. Dutch pigmented rabbits (n = 34) had their left eyes injected with herpes simplex virus type 1 3 days after, concurrently, or 3 days before intravitreal injection of either 2,000 microM compound 2242 or 480 microM ganciclovir (final concentration in the eye). Both compound 2242 and ganciclovir were equally effective compared with saline when administered simultaneously with the virus (P < 0.0001). In the 3-day pretreatment paradigm, compound 2242 was superior to ganciclovir (P < 0.04), but there was no clear difference between the two with regard to their effects on an established infection. The pharmacokinetics of compound 2242 in 10 rabbits injected intravitreally with 30 microM showed an intravitreal half-life of 8 h. This compound, which may be orally active in its pro form, has a very high therapeutic index in the eye and is more efficient than ganciclovir in this animal model of herpes retinitis.